Dendrochronological Potential of Tropical Species in the Peruvian Amazon: An Analysis in Flooded Forests of the Southeast - Miguel A. Ranilla-Huamantuco; Ingrid A. Cassana-Huáman; John Canales-Ramirez; Javier Navio Chipa; Kerly J. Macedo Enriquez; Robert F. Farfan-Huanca; Leif A. Portal-Cahuana (BioResources)
Research on growth rings in tropical trees within flooded forests has unveiled the complexity of climate change in these ecosystems. However, there has been limited understanding regarding species and their potential for dendrochronology. This study assessed 20 species from 13 botanical families in a flooded forest in southeastern Peru. Wood samples were collected during the dry season using a non-destructive sampling with motorized drill, alongside botanical samples for identification. Growth ring features were described following the IAWA, at a macroscopic level. Thirteen species showed promise for dendrochronological studies, eight of which were previously undocumented. These findings are pivotal for prioritizing species in future dendrochronological investigations in the Peruvian Amazon.